O processo de envelhecimento da pessoa com deficiência intelectual e sua família - Silva, Rosane Seeger da (2016)
The society we live in is aging; the number of elderly people has been growing in a speedy way in the last few years. The aging process of people with intellectual disability is an incipient discussion, until recently; these people did not reach this stage of life: they had low expectations. The increase in longevity brings new challenges to families, to society in general and to the State. Therefore, this research aimed to know the aging process of people with intellectual disability in a small city in the countryside of Rio Grande do Sul and its implication in family quality of life. It’s a census survey performed with a qualitative approach. Three individual questionnaires were applied: two specially designed for this study, one directed to the person with intellectual disability and the other to the person’s family member/caregiver, containing structured questions addressing social and demographic aspects: gender, age, education, occupation, economical and cultural situation. And, also, the WHOQOL-Bref, applied combined with the family/caregiver one. The study’s population was constituted by 85 people with intellectual disability (77 living at home and eight institutionalized) and 75 family members/caregivers (71 not formals and four formals). The data collected were charted, organized and registered in Microsoft Office Excel 2013 program, presented in tables and charts using mean, standard deviation, minimum value, maximum value and percentage, according to the human development phases. For the data analysis, the software SPSS 20.0 was used to create the variables. The data collection was done between April and September 2015. This present study was submitted to and approved by the CEP/UFSM with the CAAE number of 41459315.8.0000.5346. It was verified in the questionnaires application that most subjects live with people with whom they have some level of kinship: 34,11% claim to live with their parents; 25,88% reside only with their mother; 10,58% lived with brothers; 9,41% with other people; 7,05% resided in a long-term care facility for the elderly; 3,52% only with the father, 2,35% with the grandparents; 1,17% with their children and 1,17% lived alone. It stands out that 58,82% of the people researched are males and 41,18% are females, with ages varying from 1 year and four months to 74 years, with a mean age of 31,82. Relating to schooling, a low level of education was verified, 15,29% not literate; 44,70% are illiterate and 40% didn’t finish elementary school (5 years maximum of school enrollment). Most subjects, 97,64% receive clinical monitoring by several medical specialists. The results related to family members/caregivers show that they’re mostly women (82, 66%), with a mean age of 51, 56 years and with a low rate of schooling (5 years maximum of school enrollment). Relating to the quality of life of the family members/caregivers it was verified that the highest mean scores are, respectively, about the Social Domain (M=79,1; SD=10,6); followed by Physical Domain (M=74,6; SD=14,6); the Psychological Domain (M=68,8; SD=12,5) and, finally, the Environmental Domain (M=60,9; SD=11,3). It was noted that most people with intellectual disability are males, predominantly in the age group of 20-40 years old, with few schooling years and residing with family members that, by the way, show their quality of life preserved. The results of this research reveal, on one side, not very favorable conditions relating to schooling and, on the other, favorable conditions to broadened family and social living.